The impact of the practical practice method on the achievement of primary school students in Islamic Education (Journal of the College of Basic Education, 2023)
Islam used practical training as a method of education to acquire psychological characteristics.virtuous behavioral habits and values. It is noticeable that the teaching of values in schools is stillIt relies heavily on memorization and memorization without progressing to the stage of actual practice.Values lose their importance for the learners, as this method has proven to be ineffective.It is more prosperous when it is linked to situations that arise organically in the classroom, at home and at school.Some field studies confirmed that mere indoctrination of values does not lead to a modification in their behaviour.Al-Qaimi (Abdullah) (2/118: 1997).In this way, Ibn Sina shows the need to pay attention to the students' inclinations and aptitudes.Educate them and provide them with the necessary guidance when choosing the type of science that is suitable for their future life.Ibn Sina considered the study of students' inclinations as a prerequisite for improving the education process and making it a basis forto educate and guide them.Thus, we see how Ibn Sina incited Muslim teachers to search for what suits the inclinations ofand preparations, and their students were eager to teach the sciences that they would like to specialize in in the future.(Abu Jalala (132-133: 1999).The acquisition of values is ineffective unless it is transformed into directed behaviour, action and practice.Educators should be very careful to make these values tangible to the learners before theyThey are just subjects included in the academic curricula (Abdullah) 2/220-221: 1997.The more clear the educational objectives set by the teacher for both the teacher and the student, the moreThe method of selection for the teaching method was successful, and the method should suit the level of the students.And I thought that the final outcome of the educational process is building knowledge, acquiring skills, and developing inclinations.and positive attitudes towards the subject (Abu Jalala (217:1999), and these changes were reflected in the process